Interdisciplinarity and transdisciplinarity : problems and guidelines = Interdisciplinarnost i transdisciplinarnost : problemi i smjernice - Toš, Igor (Array, 2021)
The production of new scientific knowledge and practical solutions to complex problems require increasing amounts of interdisciplinary collaboration, while requirements for transdisciplinary cooperation have recently likewise become more frequent. In practice, however, they are rarely implemented adequately; what occurs instead is merely multidisciplinary collaboration. True implementation of inter- and/or transdisciplinary collaboration is often met with certain difficulties and obstacles: problems due to limited disciplinary competence, problems due to protecting knowledge and power, the problem of competence required for inter- and transdisciplinary collaboration, complexity problems, methodological problems and problems caused by differences in cultural traditions. It is necessary to acquire clear general definitions of the concepts of multidisciplinarity, interdisciplinarity and transdisciplinarity, to define and implement general guidelines for the development of multidisciplinary and transdisciplinary practice and to develop a new general culture of collaboration in research and practice of complex problem-solving.